Analisis Pengaruh Arus Globalisasi Terhadap Budaya Lokal (Indonesia) - Jadidah, Ines Tasya; Alfarizi, Muhammad Raihan; Liza, Levi Lauren; Sapitri, Wira; Khairunnisa, Nabila (Academy of Social Science and Global Citizenship Journal, 2023)
Globalization basically begins to change habits and even culture that is rooted in society, starting from changes in lifestyle and even influencing the norms and tastes of society itself. Globalization is starting to change this with the existence of affordable and easily accessible media, making it easier for people to access information from all over the world. They continue to absorb and apply all the information they receive without considering the possible impacts of globalization. This research uses qualitative descriptive methods and library research methods. Descriptive qualitative research is a research method that involves several important efforts, such as searching for and collecting references and analyzing data results to explore the topic. Globalization is a word that we often hear and see. Globalization has many impacts, both bad and good. In summary, globalization in the digital era is a complex phenomenon that requires careful attention and action to preserve local cultural diversity while being open to global influences. In conclusion, the impact of globalization on local culture in the digital era has positive and negative sides. It is important to find the right balance between responding to global trends and maintaining local cultural identity.